Comments on the Draft New Education Policy with particular reference to Teacher Education and National Research Foundation - Reddy, M.C. Reddeppa (JOURNAL OF INDIAN EDUCATION, 2019)
Government of India has sought the comments on Draft NEP 2019 submitted by the committee under the Chairmanship of Dr.K.Kasturirangan latest by 31st July 2019. Accordingly, the Indian Institute Public of Administration (IIPA), Tirupati local branch, Department of Adult and Continuing Education and Institute of Advanced Study in Education (IASE) of Sri Venkateswara University, Tirupati, conducted a Symposium on the Draft New Education Policy (NEP), 2019, focusing on higher education on 31-7-2019. I was a participant in the Symposium. After a thorough reading of the Draft on NEP, it is noted that the Draft Report contains four parts covering 484 pages viz., Part – I: School Education; Part – II: Higher Education; Part – III: Additional Key Focus Areas and Part-IV; Transforming Education. I have presented a few comments on Teacher Education and National Education Funding besides commenting on two additional key focus areas viz., Vocational Education and Adult Education in the symposium. In this paper, I tried to provide the comments on Teacher Education (Chapter 15) and National Education Funding (Chapter 14) under Higher Education System, which I had made in the Symposium for wider deliberations among the Teacher Educators and also the academies/researchers.